2021
DOI: 10.3390/md19060322
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic Acid Exposure Induced Neural Tube Defects in Chicken (Gallus gallus) Embryos

Abstract: Okadaic acid (OA) is an important liposoluble shellfish toxin distributed worldwide, and is mainly responsible for diarrheic shellfish poisoning in human beings. It has a variety of toxicities, including cytotoxicity, embryonic toxicity, neurotoxicity, and even genotoxicity. However, there is no direct evidence of its developmental toxicity in human offspring. In this study, using the chicken (Gallus gallus) embryo as the animal model, we investigated the effects of OA exposure on neurogenesis and the incidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…First, experimental research on animals may not always be predictive of human responses (Australian Government, 2011; Merck & Co., 2021). The avian embryo model is frequently used, and accepted as beneficial for developmental biology, experimental embryology, and teratology studies in early vertebrates since it is similar to mammalian embryos (Drake et al, 2006; Jiao et al, 2021; Tufan et al, 2007). The windowing technique may become another lingering question under this title (Drake et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, experimental research on animals may not always be predictive of human responses (Australian Government, 2011; Merck & Co., 2021). The avian embryo model is frequently used, and accepted as beneficial for developmental biology, experimental embryology, and teratology studies in early vertebrates since it is similar to mammalian embryos (Drake et al, 2006; Jiao et al, 2021; Tufan et al, 2007). The windowing technique may become another lingering question under this title (Drake et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…With the advantage of being similar to mammalian embryos, the avian embryo model is widely used and quite valuable for developmental biology, experimental embryology, and teratology studies in early vertebrates (Drake et al, 2006; Jiao et al, 2021). Therefore, the current study aimed to analyze the effects of various sugammadex doses on NT and embryologic development by using the mentioned experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that OA can cause neuronal cell death by inducing hyperphosphorylation of a variety of microtubule-binding proteins, especially Tau protein and neurofibrillary tangles formation, resulting in changes in the neuronal cytoskeleton in vitro and in vivo [ 195 ]. It has been also demonstrated that OA can produce spatial memory impairment and neurodegeneration and cause hippocampal cell loss in rats [ 196 ].…”
Section: Mechanism Of Action and Toxicity: The Need For Predefined To...mentioning
confidence: 99%
“…Okadaic acid is produced by marine microalgae and causes toxicity in the brain. It is a polyether toxin that leads to diarrhetic shellfish toxicity (Jiao et al, 2021;Kamat et al, 2010). It is also involved in memory deficits by inhibition of synaptic activity.…”
Section: Okadaic Acidmentioning
confidence: 99%